Otroci v ljudskem izročilu Slovencev na Madžarskem - Kozar-Mukič, Marija (Etnolog. Nova vrsta (Ljubljana), 2007)
The childhood of the Porabje Slovenes in the period before the Second World War ended at the age of twelve. Until they were six, children were passive participants of folk life and only then started to play an active part in various jobs and customs. The girls from Porabje participated in just a single custom - carol singing at Epiphany. In all other customs only boys participated. Most often in carol singing and in activities originally performed by adults. In the 21st century Porabje children learn about these customs in the Slovene lessons at school and in out-of-school activities.
Keywords: Hungary; Madžarska; zamejski Slovenci; porabski Slovenci; Hungarian Slovenes; Porabje; otroci; child; ljudsko izročilo